Perbedaan Kinerja Saham Sebelum dan Sesudah Merger dan Akuisisi pada Perusahaan yang Terdaftar di BEI - Yuniar Almaidah; Ervita Safitri; Mister Candera (Epsilon Journal of Management, 2025)
This article aims to analyze the differences in stock performance before and after mergers and acquisitions in companies listed on the Indonesia Stock Exchange (IDX). The problem focuses on the impact of mergers and acquisitions on stock performance indicators, such as Stock Returns, Price Earnings Ratio (PER), Price to Book Value (PBV), and Earnings Per Share (EPS). In order to approach this problem, theoretical references from financial management and market efficiency theory are used. Data were collected through financial statements of companies undergoing mergers and acquisitions in the 2018-2020 period and analyzed quantitatively using normality tests and significant difference tests with paired sample t-tests. This study concludes that mergers and acquisitions have a significant effect on increasing several stock performance indicators, especially Stock Returns and PBV, although the impact on PER and EPS varies depending on the industry sector and market conditions. The results of this study are expected to provide insight for investors and business actors in assessing the effectiveness of mergers and acquisitions as a company growth strategy.